Psycho-Cognitive Human Deprivation: The Essence and Main Aspects - Terletska, Yuliana M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The relevance of the research is due to the need to initialize the cognitive activity of the psyche, eliminate internal obstacles and full use of its resources as well as ensure the assimilation of knowledge and skills. The article aims to reveal the essence and main aspects of psycho-cognitive human deprivation. Psycho-energetic and energetic-psycho-functional approaches were used. Within the framework of these approaches, the cognitive sphere through Psy-programs ensures the selection of information, and it is processing, the formation of the new mental, its transmission and use. Also, methods of analysis, synthesis, comparison and grouping were used. The essence of psycho-cognitive human deprivation was revealed, which is the stagnation or destructive process of the cognitive sphere of the psyche caused by either under-development, social immaturity or destruction of certain parameters of cognitive processes or lack, absence or unreliability of knowledge; psycho-sensitive, abstract-mental and mnemonic derivations as subspecies of psycho-cognitive deprivation; some features of the operational and functional activity of the cognitive sphere of the psyche of a deprived person are found out. Revealing the essence of psycho-cognitive deprivation and the definition of its main aspects will allow to develop the measures aimed, first, at its elimination and prevention; second, the development of the cognitive sphere and the full use of its resources; third, development of psy-programs using the resources of the unconscious, subconscious, conscious and superconscious in order to search for the latest knowledge, discoveries and inventions.